An Analysis on Higher Order Thinking Skill (HOTS) in Compulsory English Textbook for the Twelfth Grade of Indonesian Senior High Schools - Rezita Ayu Febriyani; Wisma Yunita; Indah Damayanti (Journal of English Education and Teaching, 2020)
This research aimed to investigate the composition of higher order thinking skill (HOTS) in language tasks of the English textbook “Bahasa Inggris SMA/MA/SMK/MAK kelas XII Edisi revisi 2018”; and to explain the dominant cognitive dimension used in this textbook. The design of this research was descriptive quantitative. Instruments of data collection were a table checklist and an analysis card. This research classified used content analysis. The researcher separated all the tasks in the textbook depending on the topics. The researcher read all the textbook tasks to find out which tasks are the results. The table form was used to identify all the tasks. The researcher identified the higher order thinking skill contained in the table form. The analysis card was used as the guideline to bring the instruction questions into an acceptable portion of higher order thinking capacity. The results showed that the composition of Higher Order Thinking Skill (HOTS) presented in the language skill tasks on the English Textbook entitled “Bahasa Inggris SMA/MA/SMK/MAK kelas XII Edisi Revisi 2018” are lower than the Lower Order Thinking Skill (LOTS). In addition, the most dominant cognitive dimension used in the language skill tasks of this textbook is remember (C1) with 41%. Hence, it is not enough if the teacher just only uses the English textbook Bahasa Inggris SMA/MA/SMK/MAK Edisi Revisi 2018 as a teaching tool to improve students HOTS ability.